2018
DOI: 10.11114/jets.v6i6.3125
|View full text |Cite
|
Sign up to set email alerts
|

Development of Subjective Well-Being Increasing Strategies Scale for Children (1-5 Ages) Their Mothers Use

Abstract: Subjective well-being is a sign of positive mental health of children. The aim of the present study is to develop subjective well-being increasing strategies scale for children whose mothers' uses are varied 1 to 5. In this study, there were 195 mothers whose mean ages were 31, 49 and standard deviation were 4,71. Satisfaction with life, positive and negative affect scales were used. Moreover, item analysis, exploratory factor analysis, reliability and validity analysis were used. According to results, the sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…In this study, another dimension of the scale was named as "satisfying children's desires". The strategy of satisfying the requests took place as a strategy in previously developed scale studies (Eryılmaz, 2010;Eryılmaz & Sapsağlam, 2018). Its involvement in this study points to a common aspect of humanity.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In this study, another dimension of the scale was named as "satisfying children's desires". The strategy of satisfying the requests took place as a strategy in previously developed scale studies (Eryılmaz, 2010;Eryılmaz & Sapsağlam, 2018). Its involvement in this study points to a common aspect of humanity.…”
Section: Discussionmentioning
confidence: 76%
“…When the literature is examined, empirical studies (Eryılmaz, 2010(Eryılmaz, , 2012a(Eryılmaz, , 2012bEryılmaz & Sapsağlam, 2018) can be seen in experimental studies aiming to increase happiness (Eryılmaz, 2014a(Eryılmaz, , 2014bFordyce, 1983) and theoretical explanations (Buss, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diğer yandan sıra ortalamaları dikkate alındığında evli öğretmenlerin psikolojik iyi oluş ve mutluluk artırıcı strateji kullanımı puan sıra ortalamalarının bekarlara göre daha yüksek olduğu görülmüştür. Eryılmaz ve Sapsağlam (2018) çalışmasında, annelerin çocuklarının mutluluğunu olumlu yönde etkileyen değişik stratejiler kullandıklarına vurgu yapmaktadır. Yine yapılan pek çok çalışma evliliği depresyon, mutluluk, hayat amaçları ve psikolojik iyi olma gibi birçok kavramla ilişkilendirmektedir (Diener, Gohm, Suh ve Oishi, 2000;Glenn ve Weaver, 2001;Kim ve McKenry, 2002;Lee, Seccombe ve Shenan, 1991;Marks ve Lambert, 1998;Stack ve Eshleman, 1998;Yeşiltepe ve Çelik, 2014).…”
Section: Tartışma Ve Sonuçunclassified
“…According to Seligman (2011) and Kern et al (2015) , subjective well-being is a multifaceted construct, consisting of positive emotions, engagement, positive relationships, meaning, and accomplishments. It has been shown that reduced SWB can affect an administrator's physical health, physiological performance, creativity, and problem-solving skills, which might lead to problematic psychological states, including stress disorders and low levels of work engagement ( Eryilmaz and Sapsaglam, 2018 ; Diener and Chan, 2011 ). In addition to job-related health issues and negative affects, school administrators' poor SWB is associated with social problems among teachers and students ( Kern et al, 2015 ; Riley, 2015 ).…”
Section: Introductionmentioning
confidence: 99%